Теория гибридных электронных приборов мм диапазона - Одаренко, Е. Н.; Шматько, А. А. (Weber Co., 2000)
The results of research of the electronic - wave interaction efficiency in the 0 - type hybrid device of millimeter and submillimeter waves are presented. The amplifier scheme with non resonance partitioned output stage is considered, in which the slow-wave system can be allocated on the different sides of planar electrodynamic structure. Results of the gain and efficiency calculations are presented on the basis of the combined nonlinear two-dimensional theory of a hybrid amplifier.
Keywords: гибридный электронный прибор; нелинейная теория; приборы О-типа